Implementasi Pembelajaran Contextual Teaching And Learning Melalui Metode Observasi Laboratorium Dan Lingkungan Untuk Meningkatkan Sikap Ilmiah Dan Berpikir Kritis Siswa - Rohimbun Rohimbun; Sulistyono Sulistyono; Asep Ginanjar Arip (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
This research is motivated by students' critical thinking skills in processing information while the learning process is still low. The purpose of this study is 1) to describe the implementation of learning by implementing contextual teaching and learning models through laboratory observation and environmental methods on scientific attitudes and critical thinking of students, 2) to obtain implementation data in contextual teaching and learning models through laboratory observation methods and the environment can improve scientific attitude, 3) to determine the implementation of contextual teaching and learning models through laboratory observation and environmental methods can improve critical thinking skills, 4) to uncover students' responses to the implementation of contextual teaching and learning models through laboratory and environmental observation methods on scientific attitudes and critical thinking students. The method used in this study is a mixed method (mixed methods research design). With the sampling technique using cluster random sampling, there were 2 classes, each of which amounted to 30 students for the experimental class and 30 students for the control class. The research instrument used was task and rubric students' scientific attitudes, essay tests of critical thinking skills, student response questionnaires to learning and observation sheets of teacher and student activities. The data analysis technique used is the normality test, homogeneity test and hypothesis test. Based on the results of the analysis of hypothesis testing shows the value t = 4.476 with Sig. 0.001 0.05 means that the implementation of the contextual teaching and learning model through laboratory observation methods and the environment can improve scientific attitudes. Based on the results of hypothesis testing shows the value t = 8.486 with Sig. 0.001 0.05 means that the implementation of the contextual teaching and learning model through laboratory and environmental observation methods can improve critical thinking skills in plant material at SMA 1 Darma Kuningan. The conclusion in this study is the implementation of contextual teaching and learning through laboratory observation and environmental methods to improve scientific attitudes and critical thinking of students in plant classification material at SMA 1 Darma KuninganKeywords: Contextual teaching and learning; Laboratory observation methods and environment; Scientific attitude; Critical thinking